COMPLEX ANALYSIS OF FINANCIAL CONSEQUENCES OF LABOR MIGRATION - Михайлишин, Богдан (Socio-economic relations in the digital society, 2019)
The article deals with theoretical and methodological principles of financial consequences of labor emigration from Ukraine and with a methodical approach to their measurement and calculation. The system of main financial consequences has been formed and it is proposed to classify them as direct and indirect, allowing to distinguish their nature separately and as a whole system. Еmphasizes the possibility of calculating such direct financial consequences of labor migration as a money transfer of migrants, a reduction of the burden on the state employment service fund, a reduction in the production of the gross domestic product and the following indirect financial consequences of labor migration in the monetary equivalent: opening of own affairs, investments of migrants in mobile and real estate, educational and medical industry. The possibility of determining the financial consequences of labor migration through the analysis of the number of  residential buildings commissioned, the purchase of cars and the estimation of households’ savings of labor migrants in the form of bank deposits and the assessment of the multiplier effect of these processes is also considered. The financial implications of labor migration which have a social component are analyzed. These include the increase in social payments aft er the return of migrant workers to their homeland. Widespread is the phenomenon of families’ destruction due to the migration of one of the family members and as a consequence the process of «social orphanhood». The costs of social assistance and social programs for the rehabilitation of such orphans are assumed by the state. Labor migration also results in the loss of emigrants’ skills as they carry out low-skilled labor abroad. Upon returning to their homeland, the restoration and upgrading of re-emigrants’ skills will become another article of the state budget expenditures. In the view of the existence of certain gaps in scientific researches, methodical approaches to the definition and evaluation of financial consequences are developed. According to the results of the study, it has been concluded that the developed  methodological approach could estimate the financial consequences of labor migration approximately and refl ect their amounts in monetary terms.
Keywords: financial implications; labor migration; money transfers; methodical approach; balance of financial consequences of labor migration